Edukasi Kesehatan Mental sebagai Upaya Pencegahan Masalah Psikologis pada Mahasiswa Fakultas Ilmu Kesehatan - Ria indah kusuma pitaloka Ria indah kusuma pitaloka (Badan Usaha Milik Desa Berkaho Pungpungan, 2026)
Mental health problems among university students are an issue that is receiving increasing attention, particularly among students of the Faculty of Health Sciences who face high academic and clinical practice demands. Limited understanding of mental health and strategies for preventing psychological problems can negatively affect students’ well-being and academic performance. This community service activity aimed to enhance the knowledge, awareness, and skills of students of the Faculty of Health Sciences at UNUGIRI regarding the importance of maintaining mental health as a preventive effort against psychological problems. The implementation methods included socialization, training, and evaluation. The socialization stage was conducted through the delivery of educational materials and interactive discussions, while the training focused on strengthening basic skills in managing stress and emotions. Evaluation was carried out using pre-tests and post-tests to measure improvements in participants’ knowledge. The results showed an increase in the average knowledge scores of students after the educational intervention, indicating a significant improvement in understanding. In addition, students demonstrated more positive attitudes toward mental health issues. It can be concluded that mental health education through socialization and training is effective in improving students’ mental health literacy. This activity is expected to serve as a sustainable community service model to support student mental health in higher education institutions.